Faktor Pendukung Perpindaha pada Transaksi E-Wallet dengan Pendekatan Technology Acceptance Model - Risnawati, Risnawati; Ikhwana, Andri (Institut Teknologi Garut, 2024)
This research aims to determine the factors supporting the movement of transactions. Users of electronic wallets (e-wallets) are increasing, thanks to the Financial Services Authority (OJK) which is filling the gap in the form of cooperation in the financial services sector. The benefits, ease of use, dangers and level of comfort felt by each user are different as a result of the increasing use of this e-wallet. As a result of this justification, researchers are interested in looking at the impact of variables using the Technology Acceptance Model from the perspective of user behavior in using digital wallets (e-wallets), including factors such as perceived trust, perceived security, perceived ease of use. ), perceptions of promotion, and also the addition of perceived risk (behavioral intention to use) in Garut City. The benefits of this research for e-wallet money users. The findings of this research provide food for thought that can be considered when encouraging the choice to utilize e-wallet money for payment transactions. From the results of this research, there are also 7 indicators which are supporting research factors for the shift to e-wallet transactions, including payment methods, top up and transfer methods, personal data, application usage, Cashbac, Discounts as well as ineffective and efficient. Then, based on the results of research using the factor analysis method, from 7 indicators to 6 dominant indicators to determine the transfer factors in e-wallet transactions, namely easy and practical, transaction methods, giving discounts, usage constraints, personal data security and promotional strategies. As for the risks of using e-wallet transactions, the multiple linear regression analysis test proves that problems with application use, ineffectiveness of e-wallets, and rejected transactions are of significant value. It can be concluded that the hypothesis is accepted, which means that risk perception has a negative effect on the movement of e-wallet use in Garut Regency.